Шляхи активізації інноваційної політики в Україні - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Бровко, Є. І.; Brovko, Y. E.; Карпенко, Н. О.; Karpenko, N. (Education and Science, 2019)
Матеріали науково-практичної конференції присвячено виявленню шляхів активізації інноваційної політики в Україні. Визначено сутність та природа інновацій, їх роль в економіці України. Досліджено мету та стратегії інноваційної політики, а також заходи державної інноваційної підтримки. The materials of the scientific-practical conference are devoted to identifying ways of activating innovation policy in Ukraine. The essence and nature of innovations, their role in the economy of Ukraine are determined. The purpose and strategies of innovation policy, as well as the measures of state innovation support are investigated.
Ways to activate innovation policy in Ukraine
Keywords: фінансовий стан підприємства; financial status; прибутковість; profitability; ліквідність; liquidity; майновий стан; property condition; фінансова стійкість; financial stability; ділова активність; business activity